Associations between Emotional Eating and Metabolic Risk Factors at Adolescents with Obesity - Sayin, Fatma Kubra; Buyukinan, Muammer; Arslan, Derya; Deniz, Cigdem Damla (International Journal of Child Health and Nutrition, 2020)
Purpose: This study aimed to determine whether emotional eating (EE) and uncontrolled eating (UCE) scores affect the metabolic risk factors in obese adolescents. Methods: A sample of 100 adolescents have BMI-SDS between 1.41 and 2.83 (aged 12-17 years) was selected. EE and UCE scores were estimated using the TFEQ21. The association of EE and UCE with anthropometric data, lipid profile, glucose profile, liver enzymes, and inflammation factors was assessed in boys and girls. Results: Using Spearman rank correlation, EE scores significantly correlated with uric acid (r = 0.393 and P = 0.001), CRP (r = 0.273 and P = 0.017), TG (r = 0.317 and P = 0.001), TC (r = 0.258 and P = 0.019) and VAI (r = 0.276 and P = 0.034). Also UCE scores were showed positive correlation with CRP (r = 0.257 and P = 0.024). Conclusion: In conclusion, interrelationships tend to exist between EE and triglyceride, uric acid, visceral adiposity index, and CRP levels among obese adolescents.